Answer:
7
Step-by-step explanation:
Answer: -13w - 7
Step-by-step explanation:
-6w + (-8) + 1 + (-7w)
Combine the like terms
-8 + 1 = -7
-6w + (-7) + (-7w)
-6w + (-7w) = -13w
-13w + (-7)
However, because adding a negative number is the same as subtracting the number as a positive, you can just make it -13w - 7
Answer:
formula: y-y1 = m(x-x1)
Step-by-step explanation:
General:
1. find 2 points directly on the line and apply the formula y2-y1 over x2-x1 this answer equals m
2. then add it into the formula y-y1 = m(x-x1) remember x and y are variables so only put numbers in y1 and x1
3. solve the problem
Example:
line 1:
1. y2-y1 over x2-x1 is 4-6 over 6-4 = -1
2. y-6 = -1(x-(-4) or y-6 = -1(x+4)
3. y-6 = -1x-4
4. y = -1x-2
3. the gradient equals: y = -1x-2
Hope this helps :) Let me know if you need a better example
Answer:
when x = 3, x would equal 3 since x can be substituted as 3, aka chancge any xes into 3 if they give you yhat info
Step-by-step explanation:
Answer:
y=mx+b
y=-4/5x+5b
Step-by-step explanation:
(0,-5)
(-5,-1)
-1+5 is 4
-5-0 is -5
-4/5 is the slope
use one of the points and substitute x to find the y intercept, which gives you the full equation, which is y=-4/5x+5